IDEOLOGY IN THE POETRY ANTHOLOGY 'FIRE IS NOT A COUNTRY' BY CYNTHIA DEWI OKA - WULANDARI, SITI; PUTRA, AIDIL SYAH; SUTIKNO, EKA UGI (Linguists : Journal of Linguistics and Language Teaching, 2025)
The limited academic attention to the ideological dimensions of diasporic poetry—particularly the works of Indonesian diaspora poets—reveals a critical gap in contemporary literary studies. This research aims to explore how poetry functions not only as an artistic expression but also as an ideological medium that articulates hybrid identities, intergenerational trauma, and resistance to dominant narratives. Using a qualitative descriptive method and a Thematic Discourse Analysis approach, this study examines how the anthology Fire Is Not A Country by Cynthia Dewi Oka constructs ideological meaning through poetic language, literary devices, and narrative structure. The analysis focuses on eight selected poems that highlight recurring themes such as identity, family, migration, and trauma, which are intricately intertwined in representing the complexity of diasporic subjectivity and critiquing hegemonic socio-political structures. The findings indicate that Oka’s lyrical strategies effectively infiltrate and challenge dominant ideologies—such as nationalism, patriarchal family expectations, and assimilationist pressures—while offering a counter-discourse that empowers marginalized communities through cultural articulation and collective healing.